The role of industries in providing basic life-skills education to unskilled black employees in the Empangeni/Richards Bay industrial areas - Ncube, Thenjiwe Patricia (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2001.